The relationship between tirasemtiv serum concentration and functional outcomes in patients with ALS. Issue 7 (December 2013) - Shefner, Jeremy M.; Wolff, Andrew A.; Meng, Lisa
Abstract: Tirasemtiv is a fast skeletal muscle activator that increases efficiency of muscle contraction. Both single and repeated dose studies suggested beneficial effects on measures of function, muscle strength and endurance. As the outcomes measured were identical in previous studies and the duration of all studies was 21 days or less, we pooled data from all studies and assessed the relationship between outcomes and plasma tirasemtiv concentration to assess consistency of observations as well as to increase sensitivity. We pooled data for ALSFRS-R, three pulmonary function measures, quantitative muscle strength, and submaximal handgrip endurance. Up to 855 values from 143 patients were plotted against tirasemtiv concentrations. Linear associations between tirasemtiv concentrations and changes from baseline of clinical measures were estimated using a repeated-measures mixed model. Trends toward improvement were noted in all measures except for vital capacity, despite the fact that time was not included as a factor so that any time-related decline acted to reduce the magnitude of any noted trend. In conclusion, tirasemtiv appears to have concentration-dependent beneficial effects on both function and measures of strength and endurance when administered for up to 21 days, even when time is eliminated as a cofactor. These findings further support the development of this agent in ALS.